Meningkatkan Pemahaman Konsep Matematika Siswa Sekolah Dasar melalui Pembelajaran Role Playing Berbantuan Uang Lipat (Uang Nilai Tempat) - Azizah, Lina Nur; Rahmawati, Puji; Purnanto, Arif Wiyat; Ulfa, Widya Widiania (Mitra PGMI: Jurnal Kependidikan MI, 2024)
Based on the results of pre-research observations at SD Negeri Depok 1 Sleman, it is known that some students have not reached the minimum completeness criteria (KKM) that have been determined by the school, namely 80. This research aims to determine the increase in understanding of Mathematics concepts for class II students at SD Negeri Depok 1 Sleman regarding addition. and reduction through role playing learning assisted by folding money. The research method used is classroom action research (PTK). Data collection for this research used test question sheets and teacher observation sheets. The data analysis method used is descriptive qualitative and and quantitative descriptive. The results obtained showed that teacher activity in cycle I was 66.67% (good) and increased in cycle II to 86.67% (very good). The average understanding of Mathematics concepts in cycle I obtained a score of 67 and increased in cycle II to 76.89. Completeness of the test results for understanding Mathematics concepts in cycle I was 57.14% and increased in cycle II to 78.57%. The results of this research indicate that the role playing learning model assisted by folding money media can improve students' understanding of mathematics concepts.